2017
DOI: 10.3310/pgfar05160
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anorexia nervosa: a multimethod investigation translating experimental neuroscience into clinical practice

Abstract: BackgroundAnorexia nervosa (AN) is a severe psychiatric condition and evidence on how to best treat it is limited.ObjectivesThis programme consists of seven integrated work packages (WPs) and aims to develop and test disseminable and cost-effective treatments to optimise management for people with AN across all stages of illness.MethodsWP1a used surveys, focus groups and a pre–post trial to develop and evaluate a training programme for school staff on eating disorders (EDs). WP1b used a randomised controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 353 publications
0
37
0
Order By: Relevance
“…Based on this evidence, it seems plausible to state that technology-based guided self-help for anorexia nervosa is acceptable and is not associated with lower adherence than standard treatment. A recent study also found that an online, guided self-help intervention designed to prevent relapse from intensive treatment was beneficial in the aftercare of inpatients with anorexia nervosa (Schmidt et al, 2017). However, these findings cannot generalize to the use of standalone online interventions to replace standard treatment or as only form of support after care in anorexia nervosa.…”
Section: Clinical Implications and Limitationsmentioning
confidence: 97%
“…Based on this evidence, it seems plausible to state that technology-based guided self-help for anorexia nervosa is acceptable and is not associated with lower adherence than standard treatment. A recent study also found that an online, guided self-help intervention designed to prevent relapse from intensive treatment was beneficial in the aftercare of inpatients with anorexia nervosa (Schmidt et al, 2017). However, these findings cannot generalize to the use of standalone online interventions to replace standard treatment or as only form of support after care in anorexia nervosa.…”
Section: Clinical Implications and Limitationsmentioning
confidence: 97%
“…Data were collected from clinical notes for adolescents aged 13-17 years with an eating disorder in all services beyond primary care across London. 32 Admission rates in the London study, which excluded admissions for medical stabilisation, were significantly different between groups, being 15% among those assessed and treated in a specialist service, 19% among those receiving a non-specialist assessment but treated in a specialist service and 40% among those assessed and treated in a non-specialist service. Those referred to non-specialist outpatient services were also found to have incurred approximately twice the costs of those referred to specialist services, with no statistically significant differences in outcome.…”
Section: Cost-effectiveness Of Specialist Versus Generic Servicesmentioning
confidence: 94%
“…31 Similarly, a more recent study found that service costs in a population of adolescents with eating disorders were driven by hospital admissions. 32 Thus, although our approach was narrower than that usually adopted for an economic evaluation (i.e. excluding broader health and social care services), it was considered appropriate to minimise respondent burden while still providing evidence of the key costs in this population.…”
Section: Health Service Usementioning
confidence: 99%
“…A feasibility trial 13 in the UK found tentative evidence for the efficacy of a manual-based emailguided self-care programme in preventing relapse following inpatient treatment compared to TAU. An RCT by Jacobi et al 32 examined an internet-based relapse prevention (IN@) for women with BN following inpatient treatment, again compared to TAU.…”
Section: Relapse Preventionmentioning
confidence: 99%
“…Some researchers have argued that self-help interventions are contraindicated in anorexia nervosa (AN) due to the ego-syntonic nature of the disorder and high medical risk 8,9 . However, a small body of evidence suggests that people with AN can benefit from self-help programmes enhancing treatment motivation as an adjunct to face-to-face treatment 10,11 or for relapse prevention 12,13 By comparison, self-help is a widely used treatment option for BN and BED where it has a sizeable evidence-base. In the UK, guidelines of the National Institute of Care and Excellence (NICE) recommend self-help interventions as the first step for treatments for 'bulimic-type' disorders, including bulimia nervosa (BN), binge eating disorder (BED), and milder forms of binge eating 14 .…”
Section: Introductionmentioning
confidence: 99%